A fully autonomous platform for power measurement of environmental RF sources based on a time domain readout. (1st December 2020) - La Rosa, Roberto; Trigona, Carlo
Highlights: Power Measurement of Environmental RF Sources based on a Time Domain Readout. A Fully Autonomous Measurement Platform. Battery-free wireless Measurements System. Abstract: The introduction of Internet of Things (IoT) technologies, connected and synchronized devices, and smart solutions have brought tremendous technological advancements in global communication. The increasing demand for innovative measurement systems, smart sensing nodes and battery-less instruments is challenging instrumentation and measurement industries to improve communication, power budget and the efficiency in Wireless Sensor Nodes (WSN). In this context, this paper aims to contribute to the state of the art with an energy autonomous platform for power measurement in RF environments. The architecture is a self-sustained, battery-free Radio Frequency (RF) measurement system with a time domain record that it can transmit to receiving stations through appropriate IoT channels. This paper discusses the viability of a battery-free measuring device capable of initiating measurement activity only when ambient RF power levels rise above set thresholds. The paper presents the working principles through modeling, simulation and experimental characterization in order to demonstrate the validity of the proposed method.